2019
DOI: 10.1177/0033688219845933
|View full text |Cite
|
Sign up to set email alerts
|

Perceived versus Measured Teaching Effectiveness: Does Teacher Proficiency Matter?

Abstract: The impact of the non-native speaker’s (NNS) language proficiency on their personal teaching performance has often been an issue in TESOL teacher education programmes. To explore this issue a study was conducted to investigate the link between language teachers’ language proficiency and their teaching effectiveness. Classes taught by eight NNS teachers teaching the same or similar content were observed. Teaching effectiveness and teacher language proficiency were measured both through self-ratings and by indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Lecturers' experiences also can influence their ability to adapt to the recent condition and implement their insight and skills whenever needed. The findings supported by the statements of some scholars that stated that lecturers' professional experiences will support teaching and learning process since the lecturers can offer more alternatives based on learning conditions to provide more language input during lesson activities (Choi & Lee, 2016;Moradkhani et al, 2017;Sadeghi et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Lecturers' experiences also can influence their ability to adapt to the recent condition and implement their insight and skills whenever needed. The findings supported by the statements of some scholars that stated that lecturers' professional experiences will support teaching and learning process since the lecturers can offer more alternatives based on learning conditions to provide more language input during lesson activities (Choi & Lee, 2016;Moradkhani et al, 2017;Sadeghi et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
“…They stated that teachers' general proficiency significantly impacts the promotion of language learning process. Besides, Sadeghi et al (2019) conducted a research in Iranian context. They investigated 8 Iranian teachers to see the link between their English proficiency and the way they use the language to engage learners in classrooms.…”
Section: Language Proficiency Of Teachersmentioning
confidence: 99%
“…In the private sector, the situation is much better; however, teachers are primarily recruited based on their English proficiency and knowledge of teaching methods rather than their teaching potential. While language proficiency is an important predictor of the success of teaching, effective teachers need other competencies that should be considered in a teacher recruitment process ( Sadeghi et al., 2019 ); furthermore, a high language proficiency does not automatically translate into good teaching ( Richards 2015 ).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Similar studies need to be supplemented with other data collection tools such as interviews with teachers and authorities, observations and other measures of performance indicators than self-reports in order to have more comprehensive findings. Research has shown that teachers do not necessarily carry out what they assume to be doing in the classroom (Sadeghi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%